Year-Round Avian Diversity and Seasonal trends at Sam Higginbottom University of Agriculture, Technology and Sciences (SHUATS) Campus - Tiwari, Shivam (Indian Forester, 2025)
This study analyses the diversity of bird species on the Sam Higginbottom University of Agriculture, Technology and Sciences (SHUATS) campus by analysing observation data from the author's eBird account. The authors compiled all checklist records for the SHUATS hotspot (Prayagraj, Uttar Pradesh) and documented species richness and seasonal occurrence patterns. In total, 63 bird species were recorded by the author's 31 checklists (up to Apr 2025), while the eBird database lists 144 species for the campus (419 checklists) (Bird List – Sam Higginbottom University of Agricultural Technology and Sciences (SHUATS), Prayagraj, Uttar Pradesh, India – eBird Hotspot) (eBirders – Sam Higginbottom University of Agricultural Technology and Sciences (SHUATS), Prayagraj, Uttar Pradesh, India – eBird Hotspot). Species richness was highest during the cooler months, coinciding with winter migrants and waterbirds, and lower in the hot season. Commonly observed birds included jungle babbler, doves, black drongo, and myna, while occasional visitors included winter migrants (e.g. stints, pratincoles) and wetland species. These findings align with previous surveys showing rich avian fauna in university campuses (Avian biodiversity in spring at SHUATS campus, Prayagraj, India: A survey) ((PDF) Study of Bird Diversity in Gorakhpur University Campus). The results highlight the ecological value of the SHUATS campus and demonstrate the utility of eBird citizen-science data for monitoring urban bird diversity.